The Influence of Employee Competency and Work Discipline on Technology Use Effectiveness in Palm Oil Mills - Indah Silviani Putri; Fachrizal; Yose Andre Sinuaji (Sakura Digital Nusantara, 2026)
This study aims to analyze the influence of employee competency and work discipline on the effectiveness of palm oil processing technology use at PT ANJ Binanga. The research was conducted from February to April 2026 using a quantitative method with an associative causal approach. The population consisted of employees working in the processing section of the palm oil mill, with a total sample of 53 respondents selected using accidental sampling. Primary data were collected through questionnaires measured using a Likert scale, while the data were analyzed using multiple linear regression with the assistance of SPSS. The results show that employee competency has a positive and significant effect on technology use effectiveness, with a regression coefficient of 0.278 and a significance value of 0.005. Work discipline also has a positive and significant effect, with a regression coefficient of 0.535 and a significance value of 0.000. These findings indicate that work discipline has a stronger influence than employee competency on the effectiveness of technology use. The F-test result shows that employee competency and work discipline simultaneously have a significant effect on technology use effectiveness, with an F-value of 13.052 and a significance value of 0.000. The coefficient of determination indicates that both independent variables explain 34.3% of the variation in technology use effectiveness. Therefore, improving employee competency and strengthening work discipline are important strategies to optimize the use of processing technology in palm oil mills.